ANALISIS PERAN BADAN KELUARGA BERENCANA DAN PEMBERDAYAAN PEREMPUAN DALAM PENGENDALIAN PERTUMBUHAN PENDUDUK DI KECAMATAN ENREKANG KABUPATEN ENREKANG - Ikbar Ikbar (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2017)
The purpose of the study was to determine the role and function as well as the factors that influence BKBPP in controlling population growth in Enrekang District, Enrekang Regency. Data collection techniques used in this study were interviews, questionnaires, and observation. The collected data was then analyzed using frequency and percentage tables. The population in this study are employees at the BKBPP office and the community in Enrekang District, Enrekang Regency. Sampling was carried out by proportional sampling in this study as many as 50 people, namely 10 employees at the BKBPP office and 40 people selected according to the requirements of the community. The results show that the role of BKBPP is considered to be quite instrumental in controlling population growth in Enrekang District, this is shown from the results: policy formulation as much as 61.5%, implementation of work programs as much as 55.25%, facilities and work program development as many as 60 %, early marriage as much as 45.5%, utilization of government programs as much as 72%, high birth rate as much as 47%.